An evaluation of safety and efficacy of nadifloxacin 1% ointment versus mupirocin 1% ointment in Indian children with skin and soft tissue infection - Janbandhu, Swapnil; Chaudhary, Sushil; Chaudhary, Sunil; Puppalwar, Gaurav; Jain, Rishi (International Journal of Contemporary Pediatrics, 2020)
Background: Although nadifloxacin has been shown to be effective in the treatment of skin & soft tissue infections (SSTI), there is a paucity of data comparing its efficacy and safety with other antibacterials, especially in Indian paediatric population. Therefore, objective of this study was to compare the safety and efficacy of nadifloxacin with mupirocin in children with SSTI. Methods: This was a single-centre, open label, randomized, parallel group, comparative study in 60 children of <12 years of age with SSTI. Test group (n=30) received nadifloxacin 1% ointment and reference group (n=30) received mupirocin 1% ointment, to be applied twice daily. Patients were followed up at day 4, 8 and 15. Efficacy of the study drugs was evaluated by clinical and bacteriological cure rate. Safety was assessed by reporting of adverse events. Results: Baseline characteristics of enrolled patients were comparable between treatment groups and all 60 patients completed the study. At Day 15, 100.0% cases among nadifloxacin group and 96.7% cases among mupirocin group achieved clinical cure (p=0.313). The most common bacteria found in culture were Gram positive cocci in both the groups (86.7% in nadifloxacin and 58.8% in mupirocin group). None of the cases in any of the groups showed bacteriological presence at day 15. No adverse event was reported in any of the treatment groups during the study duration. Conclusions: Nadifloxacin was found to be equally efficacious and safe to mupirocin in the treatment of SSTI in Indian pediatric population.